Les écarts de revenus dans les espaces transfrontaliers. Des moteurs de la mobilité transfrontalière - Belkacem, Rachid (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article analyses wage disparity in cross-border spaces in the Greater Region (GR) and Upper Rhine. It is based on the results of two studies, the first funded by EURopean Employment Services-Greater Region (EURES-GR) in 2022 and the other, ongoing, funded by EURopean Employment Services-T Upper Rhine. The analysis shows that this disparity can be explained by various economic, sociological and institutional factors, which operate on various levels: micro (relating to corporate policies), macro (relating to national taxation and social security policy) and meso (relating to economic sectors and branches). It begins by showing that salaries and their various component parts are hard to define, making cross-border comparison difficult. It then signals that while wages in Switzerland and Luxembourg are very attractive, they must be balanced against the cost of living and working hours, which differ on each side of the border. The main takeaway from this analysis is that the gap between wages and the cost of living is a significant driver of cross-border working in border regions.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lohnniveau; Mobilität; Schweiz; Wohnen; Wohnungsmarkt

Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Grenzüberschreitende Ungleichheiten in der Großregion. Perspektiven und Daten - Himbert, Alexa (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „Seit über 20 Jahren sammelt und analysiert die Interregionale Arbeitsmarktbeobachtungsstelle (IBA·OIE) im Auftrag der politischen Verantwortlichen der Großregion vergleichbare und interpretierbare Daten über den Arbeitsmarkt auf dem Gebiet der Großregion und liefert damit die Grundlage für struktur- und arbeitsmarktpolitische Entscheidungen in der Großregion. Durch die lange und kontinuierliche Beobachtung gelingt es, ein deutliches Bild der Pendlerbewegungen und ihrer Profile im Kooperationsraum der Großregion zu zeichnen und diese engen Verflechtungen sichtbar zu machen. Allerdings werden auch die Unterschiede deutlich, die kulturell bedingt, aber auch durch die heterogenen Wirtschaftsstrukturen der Teilregionen gewachsen sind. Als Grundlage dienen zunächst die Daten der europäischen Statistikbehörde Eurostat, die in harmonisierter Form vorliegen und dadurch im grenzüberschreitenden Kontext leicht vergleichbar sind. Für die detaillierteren Indikatoren auf der Ebene der Großregion werden zudem die Daten der jeweiligen statistischen Ämter und anderer Datenproduzenten aus den Teilregionen herangezogen. Aufgrund unterschiedlicher Hintergründe und Erhebungsmethoden bedürfen die Zahlen einer deutlichen Kontextualisierung und meist einer Harmonisierung. Insbesondere die Daten zu den Grenzgängerströmen stammen aus unterschiedlichen Datenquellen, die einer Harmonisierung auf großregionaler Ebene bedürfen.“
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Les travailleurs frontaliers atypiques face aux inégalités transfrontalières. Éclairages et défis - Mezaroş, Mădălina; Uyttebrouck, Constance; Górczyńska-Angiulli, Magdalena; Paccoud, Antoine (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article explores the dynamics of atypical cross-border workers in the Greater Region, that is to say, those who reside in a neighbouring country while maintaining employment in Luxembourg. Before highlighting the housing access inequalities that this residential dynamic entails, the analysis examines housing policies in Belgium, France, Germany and Luxembourg to better understand the disparities that intensify pressure on regional housing markets. Recent and historical data on the profiles of atypical cross-border workers are presented, along with testimonies from former residents of Luxembourg who have left the country. The study sheds light on how border housing markets respond to this growing demand, sometimes to the detriment of long-standing residents. It concludes by emphasising the need for a cross-border housing observatory to co-ordinate data collection and assess emerging inequalities, including land pressures and residential exclusion in border areas, calling for more harmonised governance to address these challenges.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Wohnen; Wohnungsmarkt

Marché du travail transfrontalier. Différentiels et interdépendances - Pigeron-Piroth, Isabelle; Schiel, Kerry (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „With its 267,300 cross-border workers in 2022, the Greater Region of SaarLorLux is often presented as a model of European integration. Borders are becoming less and less perceptible, and are disappearing for commuters travelling from one country to another. However, the Covid-19 pandemic has shown the reappearance of borders that were thought to have been forgotten. It has to be said that many border-related issues have come to the fore in recent years, all the more so because of the many challenges and tensions as well as the growing number of cross-border workers. The question of inequalities is central in this context of a cross-border labour market with strongly interwoven components.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Zum Modell des transnationalen sozialen Raums im Kontext von Grenzregionen. Theoretisch-konzeptionelle Überlegungen am Beispiel des Grenzgängerwesens - Wille, Christian (Europa Regional, 2009)
Abstract: „Angesichts fortschreitender Globalisierung gewinnen übernationale Sozialbeziehungen zunehmend an Bedeutung. Sie rücken als Forschungsgegenstände immer stärker in die Human- und Sozialwissenschaften ein und stellen die teilweise noch an ‚verankerten’ Lebensbedingungen orientierten analytischen Konzepte in Frage. So ist teilweise ein Wandel weg von statischen, homogenisierenden und abgeschlossenen Modellen von Gesellschaft, Kultur und Raum hin zu entsprechend offenen und dynamischen Konzepten auszumachen. Diese können wichtige Impulse geben für Fragestellungen und ihre theoretischen Annäherungen auf der kleinräumigen Ebene von benachbarten Grenzregionen. Im vorliegenden Beitrag soll hierfür das Modell des transnationalen sozialen Raums aufgegriffen und im Hinblick auf grenzüberschreitende Sozialverflechtungen zwischen europäischen Grenzregionen theoretisch-konzeptionell diskutiert werden. Dafür werden zunächst die Mobilitätstypen des Transmigranten und des Grenzgängers erläutert und auf empirischer Ebene beispielhaft Bezüge zu einer bei Grenzgängern in der „Großregion SaarLorLux“ durchgeführten Studie hergestellt. Das im Umfeld der Migrationsforschung entwickelte und vorzustellende Modell fokussiert auf dauerhafte Sozialzusammenhänge, die über Nationalstaaten hinausreichen und neue Vergesellschaftungszusammenhänge konstituieren, gleichwohl bleibt es in seiner Konzeption und Analytik weitgehend einem statischen und nationalstaatlichen Denken verhaftet. Vor diesem Hintergrund wird versucht, die zentralen Desiderata und mögliche Entwicklungsperspektiven für die Erforschung transnationaler Sozialzusammenhänge in Grenzregionen herauszuarbeiten. Given the continuing processes of globalisation, social networks that can be categorised as being above the national level are coming to the fore. They are also making constant headway as research topics in the human and social sciences by calling analytical concepts into question that are still geared towards “rooted” life conditions. For instance, there is a move away from statistical, homogenising and closed models of society, culture and space to more open and dynamic concepts that can provide important motivation for questions and their way they theoretically approach these issues on the small-space level of neighbouring border regions. This article will address the model of a transnational social space and discuss it in the framework of cross-border social interconnections between European border regions. It will start off by explaining the types of mobility that transmigrants and cross-border commuters have and then empirically and exemplarily linking this to a study made on cross-border commuters in the large-scale SaarLorLux region. The model to be presented here has been developed in the context of migration research and it focuses on permanent social connections that go beyond national states and constitute new connections of socialisation, even though its conception and analytical methods mostly remain dedicated to static thinking and to the national state. Given these facts, this article attempts to outline the central desiderata and potential development vistas for the research on transnational social relationships in border regions.“
Keywords: Arbeitnehmer; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Pendler; Sozialraum; Transnationalisierung

Secondary labour force of permanent staff? Foreign workers in the Aachen coal mines - Klank, Kristin (TSEG - The Low Countries Journal of Social and Economic History, 2008)
Abstract: „The paper gives an overview of the recruitment and professional status of workers in the coal mining district of Aachen from different origins, i.e. local miners, miners from other German coal districts, cross-border commuters from Dutch South-Limburg and labour migrants. Migration history generally assumes that foreign workers were primarily employed as temporary workers in workplaces abandoned by the local population. This article argues that the labour market situation of foreign commuters and labour immigrants has to be studied separately. Commuters were primarily skilled miners, who came to the mines on their own account. After the First World War, labour mobility between the Aachen region and South-Limburg was ephemeral and often resulted from sudden institutional changes. In general, long distance labour migrants were unskilled. They arrived in the mines in large groups hired directly by agents of the mines or mediated by the Federal Employment Office. The position of foreign immigrants underwent important changes. During the first recruitment drives of the Aachen mines between 1906 and 1912, immigrants were indeed considered as temporary workers; after the Second World War, the companies tried hard to make these workers stay beyond the minimal period of one year. Long-term labour contracts could lead to integration of immigrant workers into the permanent workforce, but also penalised workers who wished to leave prematurely.“
Keywords: Aachen (Region); Arbeitsmigration; Niederländer; Steinkohlenbergbau; Südlimburg (Niederlande)

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Werken over de grens. Limburgers naar Duitsland, 1870–1914 - Langeweg, Serge (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmarkt; Arbeitsmigration; Deutschland; Grenzarbeitnehmer; Provinz Limburg (Niederlande)